The role of the cytokinin biosynthesis pathways in the rate of tobacco leaf senescence - Węzigowska, Paulina; Trojak, Magdalena; Skowron, Ernest (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2024)
The regulation of leaf senescence depends on endogenous and exogenous factors, among them phytohormones like cytokinins (CKs). CKs are key players regulating the senescing process, as their endogenous concentration is linked to the onset and rate of senescence progression. Thus, this study aimed to identify the relationship between the activity of endogenous CKs biosynthesis pathways - the cytosolic mevalonate (MVA) and the plastid methyl-erythritol phosphate (MEP) and the rate of leaf senescence. To this end, three distinct tobacco (Nicotiana tabacum L.) cultivars – Xanthi, Golden Virginia and Monte Calme Yellow were analysed. The study involved treatment with exogenous CK – benzyladenine – and two different CK synthesis inhibitors: lovastatin and clomazone. The progression of senescence was induced by light deprivation and monitored with chlorophyll level (SPAD), photosynthetic activity (PAM) and changes in the Rubisco protein profile (SDS-PAGE). Analyses showed that the Xanthi cultivar was characterized by delayed onset of senescence and stay-green phenotype, while Golden Virginia, and particularly Monte Calme Yellow showed rapid leaf senescence. The studies provided valuable information regarding the role of MEP and MVA pathway of CK synthesis in the regulation of tobacco leaf senescence.